2004
DOI: 10.1302/0301-620x.86b1.14507
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb arthroplasty complicated by deep venous thrombosis

Abstract: The aim of this study was to determine the prevalence of deep venous thrombosis (DVT) following lower limb arthroplasty and to assess whether this adversely affected satisfaction, relief from pain, or the level of mobility as perceived by patients. Six hundred and ten consecutive recipients of primary total hip replacement (THR) or total knee replacement (TKR) underwent routine post-operative venography. The functional outcome had already been assessed at one year by using the Regional Arthroplasty Database qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 9 publications
(8 reference statements)
1
40
0
2
Order By: Relevance
“…The reported prevalence of postoperative distal DVTs is significantly higher than that of proximal DVTs in patients undergoing TKA [10]. DVTs in lower extremities commonly start in the veins of the calf, and then extend proximally to the thigh [11].…”
Section: Discussionmentioning
confidence: 98%
“…The reported prevalence of postoperative distal DVTs is significantly higher than that of proximal DVTs in patients undergoing TKA [10]. DVTs in lower extremities commonly start in the veins of the calf, and then extend proximally to the thigh [11].…”
Section: Discussionmentioning
confidence: 98%
“…9 A higher incidence of distal DVT has been found after TKA compared with THA. 3,18,19 Moreover, symptomatic VTE occurs about 11 days sooner after TKA than THA, with about one-half and two-thirds of the events being diagnosed after hospital discharge in patients who had TKA and THA, respectively. Thus, the differences in the pathogenesis and characteristics of VTE after THA and TKA should be re flected in their clinical management, such that a shorter duration (ACCP recommendation of 10 d) of thromboprophylaxis may be sufficient for patients undergoing TKA, whereas extended prophylaxis after THA is particularly important owing to the prolonged risk for VTE.…”
Section: Discussionmentioning
confidence: 99%
“…18 Another study reported that the incidence of distal and proximal DVTs was 47% and 11%, respectively, in patients undergoing TKA compared with 19% and 15%, respectively, in patients undergoing THA. 19 Although DVTs often begin intraoperatively, as shown in venographic and leg-scanning studies, some appear to start much later, frequently after hospital discharge. 9 Among patients with postdischarge VTE, some may have asymptomatic DVT early after surgery (e.g., within 1 day after TKA), which then extends to involve the proximal veins.…”
Section: Overview Of the Natural History Of Vtementioning
confidence: 99%
“…1 The prevalence of positive venographic findings of VTE was reported to be as high as 57.6% in patients undergoing TKR who did not receive chemical prophylaxis. 2 Moreover, symptomatic VTE is quite more infrequent in this population with the incidence being ranged from 0.44% to 2.6% depending on the specific characteristics of the population. 3,4 These highlight the importance of using a standardized prophylaxis regimen against VTE that will outweigh the costs of treatment since most patients with thrombosed lower extremity veins remain asymptomatic without any chemical prophylaxis within 1 year after surgery.…”
Section: Introductionmentioning
confidence: 87%